Congressman Tony Coelho Keynotes San Joaquin College of Law Graduation - Watkins, Howard::::::::: (1989)
Congressman Tony Coelho and Howard K. Watkins 1st row Seated: Hon. Hollis Best, ? Congressman Coelho and Oliver Wanger